Spatial and Cellular Characterization of mTORC1 Activation after Spinal Cord Injury Reveals Biphasic Increase Mainly Attributed to Microglia/Macrophages. (28th March 2014) - Kjell, Jacob; Codeluppi, Simone; Josephson, Anna; Abrams, Mathew B.
Abstract Mechanistic target of rapamycin complex 1 (mTORC1) is an intracellular kinase complex that regulates energy homeostasis and transcription. Modulation of mTORC1 has proven beneficial in experimental spinal cord injury, making this molecular target a candidate for therapeutic intervention in spinal cord injury. However, both inactivation and activation of mTORC1 have been reported beneficial for recovery. To obtain a more complete picture of mTORC1 activity, we aimed to characterize the spatiotemporal activation pattern of mTORC1 and identify activation in particular cell types after contusion spinal cord injury in rats. To be able to provide a spatial characterization of mTORC1 activation, we monitored activation of downstream target S6. We found robust mTORC1 activation both at the site of injury and in spinal segments rostral and caudal to the injury. There was constitutive mTORC1 activation in neurons that was biphasically reduced caudally after injury. We found biphasic mTORC1 activation in glial cells, primarily activated microglia/macrophages. Furthermore, we found mTORC1 activation in proliferating cells, suggesting this may be a function affected by mTORC1 modulation. Our results reveal potential windows of opportunity for therapeutic interference with mTORC1 signaling and immune cells as targets for inhibition of mTORC1 in spinal cord injury.